Durable Economies Organizing the Material Foundations of Society - Jaeger-Erben, Melanie; Wieser, Harald; Marwede, Max; Hofmann, Florian (Arbeit und Organisation, 2023)
Leaking water infrastructures, heritage tourism, investments in artworks, failing electronics: Durability lies at the heart of a wide range of seemingly unrelated phenomena. In today's economies, which rest on ever-larger stocks of infrastructures, buildings, machinery and household goods, durable things are both a hugely significant source of wealth and a constant source of struggle. The contributors argue that a deeper engagement with durability is essential for reaching an understanding of how economies work; and for envisaging alternative economies built on principles of environmental stewardship and social justice. Placing durability at the core of economic analysis, this volume explores the work and tensions involved in the production and valuation of durability to outline a new agenda for more sustainable economies.